2019
DOI: 10.3390/app9051008
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Demulsification of Acidic Oil-In-Water Emulsions with Silane-Coupled Modified TiO2 Pillared Montmorillonite

Abstract: Emulsified pickling waste liquid, derived from cleaning oily hardware, cause serious environmental and ecological issues. In this work, a series of grafted (3-aminopropyl)triethoxysilane (APTES) TiO2 pillared montmorillonite (Mt), Ti-Mt-APTES, are prepared and characterized for their assessment in demulsification of acidic oil-in-water emulsion. After titanium hydrate is introduced through ion exchange, montmorillonite is modified by hydrophobic groups coming from APTES. The Ti-Mt-APTES in acidic oil-in-water … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 31 publications
(28 reference statements)
0
4
0
Order By: Relevance
“…TiO 2 -based nanomaterials exhibited great potentials for the photocatalytic degradation and adsorption of organic pollutants from wastewater systems. Two papers in this issue are related to the design and synthesis of new TiO 2 -based nanomaterials for oil-water separation [7] and photocatalytic degradation of methylene blue [8]. The first paper by Zuo et al reported the design and synthesis of silane-modified TiO 2 pillared montmorillonite (Ti-Mt-APTES) for the demulsification of acidic oil-in-water emulsion [7].…”
Section: New Materials For Environmental Sciencementioning
confidence: 99%
See 1 more Smart Citation
“…TiO 2 -based nanomaterials exhibited great potentials for the photocatalytic degradation and adsorption of organic pollutants from wastewater systems. Two papers in this issue are related to the design and synthesis of new TiO 2 -based nanomaterials for oil-water separation [7] and photocatalytic degradation of methylene blue [8]. The first paper by Zuo et al reported the design and synthesis of silane-modified TiO 2 pillared montmorillonite (Ti-Mt-APTES) for the demulsification of acidic oil-in-water emulsion [7].…”
Section: New Materials For Environmental Sciencementioning
confidence: 99%
“…Two papers in this issue are related to the design and synthesis of new TiO 2 -based nanomaterials for oil-water separation [7] and photocatalytic degradation of methylene blue [8]. The first paper by Zuo et al reported the design and synthesis of silane-modified TiO 2 pillared montmorillonite (Ti-Mt-APTES) for the demulsification of acidic oil-in-water emulsion [7]. They found that the fabricated Ti-Mt-APTES materials showed improved demulsification efficiency (94.8%) when 2.5 g/L of sorbent was added into the acidic oil-in-water emulsion after 5 h. In addition, the materials characterizations and control tests proved that the electrostatic interaction between materials and oil droplets as well as the intercalation of titanium hydrate play main roles in the oil adsorption and demulsification.…”
Section: New Materials For Environmental Sciencementioning
confidence: 99%
“…The oil in oily wastewater mainly exists in the form of dissolved oil, emulsified oil, dispersed oil, and oil slick . Concentrated on various oily wastewaters, different techniques including filtration, membrane-separation technology, , biological treatment, , electro-coagulation, , adsorption , and chemical flocculation , etc. have been used to deal with oily wastewater.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas, due to the low separation efficiency, complicated manipulation, high cost, and time consumption, the applications of above-mentioned technologies are limited . Herein, chemical flocculation and adsorption have been considered as facile methods in the field of emulsified oily wastewater treatment as a result of simple operation and high separation efficiency. , At the oil/water interface, the strong adsorption between separation materials and oily droplets can transform the surface forces and the interfacial properties between emulsion droplets . For the coagulation, after the break of interfacial films, the destabilized oil droplets aggregate and form larger flocs.…”
Section: Introductionmentioning
confidence: 99%